Insulin sensitization via partial agonism of PPARγ and glucose uptake through translocation and activation of GLUT4 in PI3K/p-Akt signaling pathway by embelin in type 2 diabetic rats - Gandhi, Gopalsamy Rajiv; Stalin, Antony; Balakrishna, Kedike; Ignacimuthu, Savarimuthu; Paulraj, Michael Gabriel; Vishal, Rajagopal (Biochimica et biophysica acta, 2013)
The present study was aimed at isolating an antidiabetic molecule from a herbal source and assessing its mechanism of action. Embelin, isolated from Embelia ribes Burm. (Myrsinaceae) fruit, was evaluated for its potential to regulate insulin resistance, alter β-cell dysfunction and modulate key markers involved in insulin sensitivity and glucose transport using high-fat diet (HFD) fed-streptozotocin (STZ) (40mg/kg)-induced type 2 diabetic rats. Molecular-dockings were performed to investigate the binding modes of embelin into PPARγ, PI3K, p-Akt and GLUT4 active sites. Embelin (50mg/kg b wt.) reduced body weight gain, blood glucose and plasma insulin in treated diabetic rats. It further modulated the altered lipid profiles and antioxidant enzymes with cytoprotective action on β-cell. Embelin significantly increased the PPARγ expression in epididymal adipose tissue compared to diabetic control group; it also inhibited adipogenic activity; it mildly activated PPARγ levels in the liver and skeletal muscle. It also regulated insulin mediated glucose uptake in epididymal adipose tissue through translocation and activation of GLUT4 in PI3K/p-Akt signaling cascade. Embelin bound to PPARγ; it disclosed stable binding affinities to the active sites of PI3K, p-Akt and GLUT4. These findings show that embelin could improve adipose tissue insulin sensitivity without increasing weight gain, enhance glycemic control, protect β-cell from damage and maintain glucose homeostasis in adipose tissue. Embelin can be used in the prevention and treatment of type 2 diabetes mellitus caused due to obesity. [Display omitted] ► Embelin was isolated from Embelia ribes Burm. fruit. ► Embelin suppressed the body weight gain in type 2 diabetic rats. ► Embelin increased the PPARγ expression in epididymal adipose tissue. ► Embelin regulated glucose uptake through GLUT4 in PI3K/ p-Akt signaling. ► Embelin docked with PPARγ, PI3K, p-Akt and GLUT4.